Identifying major policy challenges and policy interventions via expert methods - Dušana Dokupilová; Vladimír Baláž; Vladimíra Čavojová Kurincová; Eva Ballová Mikušková; Dagmar Gombitová (Review of Economic Perspectives, 2020)
This paper presents the application of expert decision methods for the formulation and prioritization of the long-term economic, social and environmental policies in the Slovak Republic. The Partnership Agreement for the Slovak Republic (PA) is an underlying strategy for investments from the European Structural and Investment Funds (ESIF) in the period 2021-2027. Policies implemented under the PA will allocate exteuro13.4b on four policy objectives. This paper concentrates on the policy objective 4 'Social development'. The authors co-operated with the Deputy Prime Minister Office and assembled panels of top Slovak experts on social and economic issues. The Delphi and Analytical hierarchy process (AHP) methods were combined for analyzing major development challenges and eliciting policy priorities. The methods combined the bottom-up and top-down approaches to policy making. Nine potential policy measures in three policy areas emerged from the Delphi exercise. The AHP exercise applied three criteria (relevance, urgency and feasibility) to rank the abovementioned measures within three policy areas. As for the Policy Area 1 (Labour market, employment, training and institutions) the measure 4.1.1 "Improving access to employment and modernizing institutions and services on labour market" clearly dominated over the measure 4.1.2 "Supporting a better work-life balance". The measure 4.2.2 "Equal access to quality and inclusive education" emerged substantially more important than measures 4.2.1 "Improving the quality and effectiveness of education and training systems" and 4.2.3 "Support to life-long learning" in the Policy Area 2 "Education and skills". Finally, measures 4.3.2 "Supporting social and economic integration of marginalized Roma communities" and 4.3.3 "Ensuring equal access to healthcare including primary care" received the highest ranks in the Policy Area 3 "Health and social services".
Keywords: D78; D70; 330; Delphi method; Analytical hierarchy process; Partnership Agreement; Long-term planning